NASI KAPAU AS GASTRONOMIC TOURISM ATTRACTION IN WEST SUMATRA - Mardiyah, Siti; Yanthy, Putu Sucita; Antara, I Ketut (Asian Journal of Social and Humanities, 2023)
Nasi kapau is a famous culinary delight from West Sumatra. This cuisine is also well-known with the 'Uni' as the sellers. The 'Uni', or the female merchant, sells nasi kapau in a unique and distinguished way. Nasi kapau has developed into a culinary tourism attraction in West Sumatra in Los Lambuang and Nagari Kapau. This research aims to analyze the element of nasi kapau to improve the cuisine as a gastronomic tourism attraction in West Sumatra. This research uses a qualitative descriptive analysis method. In-depth interviews was done to five women that have experience in selling nasi kapau over 27 years. This research indicates the need for a development strategy to develop nasi kapau as a gastronomy tourism attraction. Storytelling is required to complete the missing gastronomy triangle to market nasi kapau. Collaborative governance is also essential in stakeholder collaboration in achieving research objectives. Empowering the community as human resources in tourism is also vital in developing nasi kapau as gastronomy tourism. Nasi kapau is already a renowned culinary attraction, but to elevate the cuisine into becoming gastronomic tourism attraction, certain measures are required as a strategic development to achieve this objective